2020
DOI: 10.1002/anie.202011780
|View full text |Cite
|
Sign up to set email alerts
|

A Homoleptic Alkynyl‐Ligated [Au13Ag16L24]3− Cluster as a Catalytically Active Eight‐Electron Superatom

Abstract: Anew alkynylated cluster [Au 13 Ag 16 (C 10 H 6 NO) 24 ] 3À is prepared by aN aBH 4 mediated reduction method. The AuAg clusters are confirmed by sophisticated characterization techniques.I th as au nique "Au center @Ag 12 @Au 12 Ag 4 "m etal framework which is protected by 24 atypical alkyne ligands L (L = C 10 H 6 NO). The ligands construct au nique type of motif L-(Ag)-Au-(Ag)-L at the cluster interface,w here the alkyne (CC) group of each Lw as linked by sharing an Au atom through the s bonds and each CCg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 62 publications
(21 reference statements)
2
42
0
Order By: Relevance
“…[1b] In each staple,t wo ligands adopt an m 2 -h 1 (Au), h 2 (Au) mode and the other adopts an m 2 -h 1 (Au), h 1 (Au) bridge mode with only a s interaction, forming a s(s,p/s,s)p motif ( Figure S8). Such adimeric staple motif in alkynyl-protected gold clusters was firs reported by the Wang group in Au 36 (PhC C) 24 and Au 44 (PhC C) 28 . [21] Eight tht molecules act as co-protective ligands to complete the protecting sphere through weak coordination bonds.…”
Section: Forschungsartikelsupporting
confidence: 53%
See 2 more Smart Citations
“…[1b] In each staple,t wo ligands adopt an m 2 -h 1 (Au), h 2 (Au) mode and the other adopts an m 2 -h 1 (Au), h 1 (Au) bridge mode with only a s interaction, forming a s(s,p/s,s)p motif ( Figure S8). Such adimeric staple motif in alkynyl-protected gold clusters was firs reported by the Wang group in Au 36 (PhC C) 24 and Au 44 (PhC C) 28 . [21] Eight tht molecules act as co-protective ligands to complete the protecting sphere through weak coordination bonds.…”
Section: Forschungsartikelsupporting
confidence: 53%
“…show all the expected elements,a nd the Au 4f 7/2 peaks (centered at 84.5 eV for Au 28 ,84.1 eV for Au 23 ,respectively) fall in between the values of Au I (85.4 eV) and Au 0 (84.0 eV), [24] which is attributed to presence of both Au 0 and Au I in clusters.T he transmission electron microscopy (TEM) images showed that Au 23 exists as discrete particles with an average size of ca. 2.0 nm ( Figure S15).…”
Section: Forschungsartikelmentioning
confidence: 85%
See 1 more Smart Citation
“…a) Total structure of the Au 13 Ag 16 L 24 clusters. [26] b) Negativemode ESI mass spectrum of the Au 13 Ag 16 L 24 cluster (inset:the experimental and simulated isotopic distribution patterns). c) Au@Ag 12 @Au 12 Ag 4 metal framework protectedb yalkyne groups from 24 ligands, with only CCgroups (highlighted in green) of Lshown for clarity.A uyellow or orange;A gpurple or bright green;Cgrey or green; Nblue;Ored.…”
Section: Resultsmentioning
confidence: 99%
“…Their further studies demonstrated that the Au12Ag32(SR)30 NCs, bearing an Au@Ag kernel, also showed high-activity, which confirmed their conclusion. 61 In Qin's work, 60 CeO2 supported Au13Ag16L24 NCs showed highly catalytic activity and selectivity to the A 3 -coupling reactions. In all, the doped Ag NCs show great potential in catalytic application, where the dopants bring enhancement in catalytic activity and selectivity.…”
Section: Catalysis Propertiesmentioning
confidence: 98%